Aplicación de un sistema de contabilidad agropecuaria para la hacienda San Luis, ubicada en el cantón Latacunga provincia de Cotopaxi, para el período enero-julio del año 2013 - Analuisa Iza, Vilma Rocío (2016)
Today ‘San Luis’ Farm develops its agricultural production activities, but it does not have an accounting system that lets it know precisely the record of purchase and consumption of raw materials, labor and supplies. Thus, a clear identification of revenues, costs, and expenses incurred during the production process in a specific period is necessary in order to make decisions involving an optimal use of resources. Therefore, this research study has been developed because of this necessity. For the implementation of an accounting system was necessary to apply a non-experimental methodology to obtain economic performance. Moreover, the general manager and the accountant, associated with the entrepreneurship of production activities such as broccoli and milk, were interviewed. In addition, information regarding revenues and expenses record was taken to define their characteristics and achieve the development of the proposal. Once the accounting system was applied, it determined that agricultural work on broccoli crop management and milk production represent a return since it is a good income management for this Farm. Finally, this study contributed to optimize the management of all resources required in growing broccoli and milk production.